Друг мой Момич: повести / Константин Воробьев ; [художник Б. М. Косульников] - Воробьев Константин Дмитриевич (Современник, 1988)
Экземпляры: б/ф-4 (20111017) / Инвентарный номер: 13243 / Цена: 2.60 / Авт.знак: В 75 / ББК: 84 (2Рос=Рус)6